(untitled) (Universal International Scientific Journal, 2026)
The article highlights the pedagogical foundations of developing patriotic competence in students through spiritual and educational activities. Competency-based, person-oriented and activity-based approaches are analyzed and the educational effectiveness of lessons, extracurricular activities, volunteering and digital tools is substantiated. The research results show that a comprehensive approach forms patriotism at the level of consciousness, emotions and practical activities.